Cardiovascular and metabolic responses to on-water upwind sailing in optimist sailors - Lopez, S. M.; Bourgois, J. G.; Tam, E.; Bruseghini, P.; Capelli, C. (International Journal of Sports Physiology and Performance, 2016)
Purpose: